2018
DOI: 10.6007/ijarbss/v8-i2/3897
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties Encountered by Low Proficiency ESL Students in Reading Online Academic Texts

Abstract: Reading is the key component for academic success for ESL students because they are required to read various materials in English. However, reading difficulties may become an obstacle for them to gain knowledge from online sources especially for ESL readers. Therefore, the purpose of this study is to investigate reading difficulties of low proficiency ESL students in reading online academic texts and how they solve the problems as teachers should be aware of reading difficulties the students encounter during o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Fourth, for the statement 'I have problem in reading English text', 74% of the freshmen admitted that they are agree and strongly agree to that statement. This finding was also found by Syaifudin (2015), Artini (2017), Romly, et al (2018. It also strengthened the result of second statement 'I can understand well reading English text' where most of the freshmen were disagree and strongly disagree.…”
Section: Freshmen' Need Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Fourth, for the statement 'I have problem in reading English text', 74% of the freshmen admitted that they are agree and strongly agree to that statement. This finding was also found by Syaifudin (2015), Artini (2017), Romly, et al (2018. It also strengthened the result of second statement 'I can understand well reading English text' where most of the freshmen were disagree and strongly disagree.…”
Section: Freshmen' Need Analysissupporting
confidence: 80%
“…From some of these factors, it can be formulated that the difficulties of students in mastering reading skills are: 1) language barrier; 2) psychological factors (low motivation); 3) learning environment (lecturers, friends, topics, modules); and 4) mother tongue (L1) and second language (L2). Thus, there are more than fifteen factors that encourage difficulty in reading skills (Romly, Abd Rahman, Supie, & Nasharudin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that pre-university ESL learners are selected based on their outstanding Sijil Pelajaran Malaysia (SPM) results (including English subject) that qualify them for tertiary education generally implies an idea that they should "naturally" be proficient at reading. However, a number of past research has demonstrated reading difficulty issues among Malaysian students, particularly among low proficiency ESL learners in reading online texts (Singh et al, 2023, Romly et al, 2018. The studies highlighted learners' lack of interest in English texts, poor language proficiency, limited time for reading, and demanding reading tasks as factors contributing to these reading difficulties.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Critical reading skills allow readers to think actively to come up with their ideas and interpretations (Flynn, 1989;Wilson, 2016), instead of solely relying on teachers and textbooks for answers. Otherwise, the students are at a superficial level of understanding and are easily obscured by the input of others, making it challenging for them to fully adapt to the intricacies of the language world (Romly et al, 2018;Desa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%